Fingerprint Attachment in Notary Act Minutes: Analysis of Implementation and Its Impact on Authentic Acts - Ida Ayu Ari Mahayani; I Wayan Novy Purwanto (NOTARIIL Jurnal Kenotariatan, 2025)
Urgency of attaching the fingerprints of the parties in the minutes of notarial deeds as an effort to strengthen the validity of authentic deeds and reduce the potential for legal disputes. This practice is based on the provisions of Article 16 paragraph (1) letter c of Law No. 2 of 2014 concerning the Position of Notary, which mandates notaries to attach the fingerprints of the parties as part of the minutes of the deed. Through a normative legal approach, this study analyzes the legal basis, implementation in the field, and legal impacts if these provisions are not met. The results of the analysis show that attaching fingerprints is not just an administrative formality, but has an important function in proving the presence and identity of the parties in the deed-making process. The absence of fingerprints in the minutes can potentially reduce the value of the deed's evidentiary value as an authentic deed, even opening up the opportunity for cancellation or lawsuits in the future. Therefore, attaching fingerprints must be understood as a substantive obligation that cannot be ignored. This study recommends strengthening supervision of the implementation of these obligations and increasing the understanding of notaries and the public regarding the importance of this aspect in legal protection.